THINKING CULTURAL SPACE: A MAPPING OF ’ARTICULATION’ - Rouhvand, Hassan (PEOPLE: International Journal of Social Sciences, 2017)
Articulation, as an approach, is the core pursuit of Stuart Hall in his cultural studies and a survey of its complicated dimension is the main question of this research. The paper seeks to shed a light on and investigate the interdisciplinary field of culture in which forces from diverse layers of society are in unceasing encounter and transformation in everyday life. This study is carried out by examining the significance and performance of the concept of ‘articulation’, based on two variables of ‘space’ and ‘culture’. In so doing, the researcher advocated inductive method and brought under the spotlight five pairs of key concepts in Hall’s studies. Comprehensive relational study of ’periphery & center’, ’resistant & dominant’, ’textuality & punctuation’, ’other & self’, ’local & global’ was aimed at an exploration into their modes of (inter)connectivity. The findings showed that Hall’s articulation approach to cultural studies, far from being a simple joint of elements or eclecticism, signifies a range of complicated parallel movements, namely, simultaneous struggles for positions as well as negotiation over those positions. The outcomes would likely caution the researchers against simplifying the issue by theorizing and closing the frontiers of popular culture for temporary gains.